Prevalence of Low Back Pain and Its Intensity Among Teachers of Universities in Lahore: Prevalence of Low Back Pain and Its Intensity Among Teachers - Mushtaq, Maida; Qamar, Siddiqa; Rafiq, Shazia; Zia, Sobia Zia; Mohiuddin, Maha; Ghafoor, Abdul; Saeed, Maira; Iqbal , Sajjid (Pakistan Journal of Health Sciences, 2022)
Back pain (BP) is one of the most debilitating conditions inflicting grief, discomfort, and disability to its bearer. Teachers are more at risk of having low back. As teaching requires such activities like long standing and sitting as occupational demand so making this profession more prone to develop low back pain. Objectives: To check the prevalence and intensity of low back pain in the teachers of universities in Lahore.Methods: This study was based on cross-sectional research. Total 261 participants were included in the study with systematic random sampling technique, and collection of the data is done by using an authentic scale “Owestery Disability Scale”. SPSS version 21.0 was used and frequency charts and bar charts are used. Results: Low back pain prevalence in university teachers is 56% and 44% participants were having no pain. Most of the teachers having pain were in age range of 31 to 40 years, 52.5% were females and 47.5% were male. Most of the participants who were having low back pain experienced mild pain which constitute about 86% of total respondents with low back pain. Moderate pain was experienced by 24% participants. Only 6% teachers from the sample size felt severe pain. Conclusion: There was a significant prevalence of low back pain in teachers of universities in Lahore. The intensity of pain varied from mild to severe and most of the teachers experienced mild low back pain.